With or without a koinon. The Longue Durée of Two Regional Festivals. II. The Pamboiotia and the Basileia from the Hellenistic to the Imperial Period - Tufano, Salvatore (Hyperboreus, 2023)
The paper oﬀers the second half of a comprehensive survey of the two most important Boiotian regional festivals, i.e. the Basileia of Lebadeia and the Pamboiotia of Koroneia. The author contends that these competitions had a regional impact and were performed independently of the existence of a federal government in Boiotia. This article, in particular, addresses the Hellenistic and Roman periods of these festivals. The third and the second centuries BC (Section 3), before the dismantlement of the Boiotian koinon in 171 BC, saw the great success of both the Basileia and the Pamboiotia. The Basileia were an individual competition and the federal government decided, around 221/0 BC, to declare this a sacred festival. The Pamboiotia became, from the early third century BC, a military event, because there were contests for military units and these could perform their training. This diﬀerence explains why, after 171 BC, the Pamboiotia disappeared and the Basileia continued as a local festival with a new name, Trophonia (Section 4). The ﬁrst century BC saw a new regional organization, in Boiotia, with the reprise of a koinon. The Roman koinon was not a political body but could manage regional festivals and the Boiotians as a whole decided to rename the Trophonia with their original name and to re-start the Pamboiotia. The author claims that the Roman government strongly inﬂuenced the choice to abandon the military aspects of the Pamboiotia. The external inﬂuence also explains why, in the imperial period (Section 5), the Basileia were probably renamed Kaisareia and substituted by the imperial cult in Lebadeia. The late, short fate of the new Trophonia in the third century AD is exceptional and could indicate that the Boiotian koinon now chose to focus more on the Pamboiotia as a regional festival. The cult in Koroneia is still important in the imperial period; the last clear signs of individual contests in Koroneia date to the ﬁrst century AD and in the II Century AD Koroneia was mostly a meeting point for the Boiotians. The study demonstrates that the longue durée of the Pamboiotia and the Basileia (ﬁfth/fourth cent. BC – third cent. AD) depends on the Boiotian use of these regional festivals as carriers of collective memory.